An investigation of adolescents’ emotional and behavioral manifestations and the factors influencing cases from Bulgan Province, Mongolia (Central Asian Journal of Medical Sciences, 2026)
Objective: This study aimed to investigate factors potentially influencing the mental health of adolescents. Methods: A population-based birth cohort study was conducted in Bulgan Province from 2016 to 2022. Emotional and behavioral manifestations in children were assessed using the Strengths and Difficulties Questionnaire – Mongolia (SDQ-Mongolia). Risk factors affecting emotional and behavioral outcomes among children aged 6, 9, and 12 years were analyzed using multinomial logistic regression models. Results: The study included 1,077 parent–child pairs in 2016, 890 pairs in 2019, and 781 pairs in 2022. According to maternal reports, 81.89% of children in 2016, 71.8% in 2019, and 81.05% in 2022 exhibited abnormal emotional and behavioral manifestations. Among 12-year-old children, abnormal emotional and behavioral manifestations were significantly associated with lack of parental attention (adjusted Relative Risk Ratio [aRRR] 2.0, 95% Confidence Interval [CI] 1.09–3.68), reduced sleep duration (aRRR 2.22, 95% CI 1.21–4.08), and increased mobile phone use (aRRR 3.36, 95% CI 1.02–11.0). Conclusions: Lack of parental attention, reduced sleep duration, and higher mobile phone usage are significant factors influencing abnormal emotional and behavioral manifestations among adolescents.